2018
DOI: 10.1038/s41467-018-05075-x
|View full text |Cite
|
Sign up to set email alerts
|

Designing a norepinephrine optical tracer for imaging individual noradrenergic synapses and their activity in vivo

Abstract: Norepinephrine is a monoamine neurotransmitter with a wide repertoire of physiological roles in the peripheral and central nervous systems. There are, however, no experimental means to study functional properties of individual noradrenergic synapses in the brain. Development of new approaches for imaging synaptic neurotransmission is of fundamental importance to study specific synaptic changes that occur during learning, behavior, and pathological processes. Here, we introduce fluorescent false neurotransmitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 73 publications
1
73
1
Order By: Relevance
“…With FFNs that mimic dopamine, heterogeneity in release was observed that was controlled in part by D2 receptors. Recently, FFNs were developed that can measure norepinephrine distinct from dopamine (107). Methods to measure actual neurotransmitters are also being developed.…”
Section: Optical Imaging Techniquesmentioning
confidence: 99%
“…With FFNs that mimic dopamine, heterogeneity in release was observed that was controlled in part by D2 receptors. Recently, FFNs were developed that can measure norepinephrine distinct from dopamine (107). Methods to measure actual neurotransmitters are also being developed.…”
Section: Optical Imaging Techniquesmentioning
confidence: 99%
“…Recent studies used two-photon Ca 2+ imaging to directly measure activity of NE axons in the cortex and to correlate their activity with pupil diameter and locomotion (Reimer et al 2016;Breton-Provencher and Sur 2018). Others have developed optical imaging methods to measure the binding of NE to various fluorescent indicators (Muller et al 2014;Dunn et al 2018;Feng et al 2019). However, little is known about the sensory cues that induce phasic NE-release in sensory cortex and the consequences of this release on synaptic integration in dendrites and spines, where the adrenergic receptors 85 are found (Herkenham 1987;Nicholas et al 1993;Aoki et al 1998;Wang et al 2007).…”
mentioning
confidence: 99%
“…A variety of FFNs now provide means to observe release during synaptic vesicle fusion from specific sites on axons, including striatal dopamine axons in vitro (Gubernator et al, 2009; Rodriguez et al, 2013; Pereira et al, 2016) and norepinephrine axons in vitro and in vivo (Dunn et al, 2018). Here, we introduce a new use for pH sensitive FFNs, which is to resolve release from dopamine axons in a region of very sparse innervation by ‘FFN flashes’, that is short duration calcium-dependent release transients during exocytosis as the fluorescence is unquenched upon exocytosis from the acidic vesicle lumen to the neutral extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine is known to disinhibit GPe cells (Cooper and Stanford, 2001; Shin et al, 2003), and could modulate the balance between the arky- and protopallidal pathways. The recently introduced FFN270, which is a substrate for the norepinephrine transporter (Dunn et al, 2018), is also pH sensitive and could provide means to measure properties of the sparse and widely distributed network of norepinephrine axons in the nervous system.…”
Section: Discussionmentioning
confidence: 99%